Longevity, Esthetic Perception, and Psychosocial Impact of Teeth Bleaching by Low (6%) Hydrogen Peroxide Concentration for In-office Treatment: A Randomized Clinical Trial - Fernandez, E.; Bersezio, C. [UNESP]; Bottner, J.; Avalos, F.; Godoy, I.; Inda, D.; Vildosola, P.; Saad, J. R. C. [UNESP]; Oliveira, O. B. [UNESP]; Martin, J. (Operative Dentistry Inc, 2017)
Objective: The aim was to evaluate the color longevity after nine months of in-office bleaching with gel (6% hydrogen peroxide), to compare this to a control concentration of 35% in a split-mouth study model, and to assess the dental confidence and psychosocial impact on patients. Methods and Materials: Twenty-seven patients were assessed at the nine-month recall. The bleaching procedure with 6% or 35% hydrogen peroxide gel was performed randomly in the upper hemi-arch of each patient. The color was measured at baseline and at one week, one month, and nine months after the procedure, using the Vita Easyshade spectrophotometer, the Vita classical shade guide organized by value, and Vita Bleach Guide 3DMaster. Moreover, two surveys, OHIP-Esthetics and PIDAQ, were used to assess the esthetic self-perception and psychosocial impact of the bleaching procedure. During the nine-month recall, the color was assessed before and after dental prophylaxis. Results: Twenty-seven patients participated in the nine-month recall. There was a significant difference in DE between the two groups at all times assessed (p<0.011). The DL, Da, and Db showed a difference between the two groups at all times assessed (p<0.038), except for DL from the baseline vs nine-month after prophylaxis value (p>0.20). There was no significant difference in DSGU at all times (p>0.05). There was a significant difference in OHIP-Esthetics and PIDAQ sums compared with baseline scores (p<0.03). Conclusion: The two compounds remained effective at nine months, with a slight rebound of color, and maintained their objective color difference but not the subjective color difference. Patients were satisfied with the bleaching procedure, and this had a positive impact on esthetic perception and a positive psychosocial impact at the nine-month recall.